Three-dimensional assessment of maxillary arch changes in infants with bilateral cleft lip and palate using vacuum-formed nasoalveolar molding with active screw versus conventional nasoalveolar molding appliances: a randomized clinical trial - Khadega Ali Al-Khateeb; Mai Hamdy Aboulfotouh; Fatma Abdelsayed; Wesam Mohamed; Mohamed Abd-El-Ghafour (BMC Oral Health)
Abstract Objectives This study aimed to compare the 3D changes of maxillary arches in infants with bilateral cleft lip and palate (BCLP) undergoing vacuum formed nasoalveolar molding appliance with active screw (VF-NAM) to those who received conventional Grayson (G-NAM). Methods A total of 24 BCLP infants were randomly allocated into, group 1 (n = 12) who received V-NAM and Group 2 (n = 12) underwent G-NAM appliances. In the V-NAM group, all infants received 1- 2 vacuum formed maxillary plates incorporated with active retraction screw. In the G-NAM group, Grayson’s NAM technique was followed. The nasal stents were added to the maxillary plates in both groups in the same manner to mold the deformed nasal cartilages. Sixteen items in the digital maxillary models were analyzed at T1 (pre-NAM therapy) and T2 (post-NAM therapy) using 3D software. Parametric data were analyzed using a repeated measures ANOVA test to compare between groups and assess changes within each group by time, while non-parametric data were analyzed using the Mann–Whitney U test to compare between groups and the Wilcoxon signed-rank test to assess changes within each group by time. Results By the end of this study, both groups showed no statistically significant differences in all variables associated with changes in the transverse and vertical arch dimensions except the mid-arch width in which the VF-NAM group exhibited a significantly greater change compared to the G-NAM group, with an effect size of 0.953 (CI 95%: -0.03 − 2.46). In the sagittal dimensions, A more significant decrease in the right and left alveolar cleft widths was observed in the VF-NAM group relative to the G-NAM group with effect sizes of 0.89 (CI 95%: -3.73–0.11). and 0.85 (CI 95%: -3.82 − 0.14), respectively (P < 0.05). Conversely, the G-NAM group demonstrated a significantly greater increase in the premaxillary rotation angle compared to the VF-NAM group, with an effect size of 0.875(CI 95%: -3.06 − 13.56) (P < 0.05). Conclusion Both VF-NAM and G-NAM effectively reduced alveolar cleft gaps, retracted the premaxillary segment, and normalized alveolar contour. However, VF-NAM resulted in greater reductions in cleft width and mid-arch width expansion. Conversely, G-NAM was more effective in improving premaxillary rotation. These findings may contribute to clinical decision-making in the early cleft management by guiding the selection of appliances based on individual anatomical characteristics. The use of a VF-NAM or G-NAM appliance could strategically optimize pre-surgical outcomes and enhance treatment planning in infants with BCLP. Trial registration NCT04966572 -July 8th 2021.